Early-Onset Sepsis as an Early Predictor for Retinopathy of Prematurity: A Meta-analysis - El Emrani, Salma; van der Meeren, Lotte E.; Jansen, Esther J.S.; Goeman, Jelle J.; Termote, Jacqueline U.M.; Lopriore, Enrico; Schalij-Delfos, Nicoline E. (American Journal of Perinatology, 2024)
Objective Neonatal sepsis has been established as a risk factor for retinopathy of prematurity (ROP) but previous meta-analyses have predominately focused on late-onset sepsis (LOS). This meta-analysis aims to explore the association between early-onset sepsis (EOS) and the risk of ROP.Study Design Observational studies reporting (unadjusted) data on proven EOS in neonates with ROP were included. PubMed, Embase, and Cochrane Library were searched. Proven EOS was defined as a positive blood or cerebrospinal fluid culture. Effect sizes were calculated by using logistic random-effects models and meta-regression analyses. Primary outcomes were any stage ROP and severe ROP (≥stage 3, type I, aggressive [posterior] ROP, plus disease or requiring treatment). Potential confounders explored were gestational age at birth, birth weight, small for gestational age, maternal steroid use, necrotizing enterocolitis, LOS, and mechanical ventilation duration.Results Seventeen studies reporting the incidence of proven EOS in neonates with ROP were included. Proven EOS showed no significant association with any stage ROP (odds ratio [OR] = 1.90; 95% confidence interval [CI]: 0.96–3.79, p = 0.067) but heterogeneity between studies was significantly high. Neonates with proven EOS had an increased risk for severe ROP (OR = 2.21; 95% CI: 1.68–2.90), and no significant confounders influencing this effect size were found in the meta-regression analysis.Conclusion Neonates with proven EOS are at increased risk of severe ROP. Neonatologists need to be aware that EOS is an early predictor of ROP and should adapt their policy and treatment decisions where possible to reduce ROP.Key Points
Keywords: retinopathy of prematurity; early-onset sepsis; prematurity; meta-analysis